2011
DOI: 10.3390/ijerph8083246
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive Study on Parents’ Knowledge, Attitudes and Practices on Antibiotic Use and Misuse in Children with Upper Respiratory Tract Infections in Cyprus

Abstract: Upper respiratory tract infections (URTIs) are common in children and represent a significant cause of antibiotic abuse which contributes to the development of antibiotic resistance. A survey was conducted in Cyprus in 2006 to assess parents’ and pediatricians’ Knowledge, Attitude and Practices (KAP) concerning the role of antibiotics in children with URTIs. A school-based stratified geographic clustering sampling was used and a pre-tested KAP questionnaire was distributed. A different questionnaire was distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
190
7
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(224 citation statements)
references
References 27 publications
(34 reference statements)
24
190
7
3
Order By: Relevance
“…Many studies highlighted a general lack of knowledge on the correct use of antibiotics by parents of paediatric age children. [10][11][12][13][14][15][16][17][18][19] This could lead to an inappropriate administration of antibiotics to children, given that from 10% to 60% of parents declare to administer antibiotics without medical prescription. [11][12][13]15,19 Moreover, several studies demonstrated that attitudes of parents could influence the decision of the paediatrician about the prescription of an antibiotic, making the lack of knowledge of the parents about this issue even more dangerous.…”
Section: Demonstrated That Streptococcus Pneumoniaementioning
confidence: 99%
See 2 more Smart Citations
“…Many studies highlighted a general lack of knowledge on the correct use of antibiotics by parents of paediatric age children. [10][11][12][13][14][15][16][17][18][19] This could lead to an inappropriate administration of antibiotics to children, given that from 10% to 60% of parents declare to administer antibiotics without medical prescription. [11][12][13]15,19 Moreover, several studies demonstrated that attitudes of parents could influence the decision of the paediatrician about the prescription of an antibiotic, making the lack of knowledge of the parents about this issue even more dangerous.…”
Section: Demonstrated That Streptococcus Pneumoniaementioning
confidence: 99%
“…[11][12][13]15,19 Moreover, several studies demonstrated that attitudes of parents could influence the decision of the paediatrician about the prescription of an antibiotic, making the lack of knowledge of the parents about this issue even more dangerous. 14,20 To date no studies have evaluated knowledge and attitudes on antibiotics among parents of children aged between 0-14 years in Italy. It should be noted that in 2011, this Country had one of the highest consumption of antibiotics in Europe, preceded only by Greece, Cyprus, France and Luxembourg, with a consequent increased likelihood of inappropriate assumptions.…”
Section: Demonstrated That Streptococcus Pneumoniaementioning
confidence: 99%
See 1 more Smart Citation
“…The unnecessary use of antibiotics is a worldwide public health issue (Alumran, Hou & Hurst, 2013;Lucas et al, 2015;Dwibedi et al, 2015;Kutty, 2011;Llor & Bjerrum, 2014;Rouusounides et al, 2011). There are multiple factors that cause concern regarding unnecessary antibiotic use, including complications related to antibiotic resistant bacteria, side effects of antibiotic use, and the possibility that antibiotics will become ineffective against bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Within the preschool population, unnecessary antibiotics are most commonly prescribed for viral upper respiratory infections (URIs) (Clavenna & Bonati, 2011;Kutty, 2011). Upper respiratory tract infections (URIs) include viral rhinitis (the common cold), influenza type A and B, acute viral rhinosinusitis, non-streptococcal tonsillitis, and pharyngitis (Boonacker et al, 2010;Rouusounides et al, 2011), and account for the highest number of emergency visits and the second highest number of primary care and outpatient visits in children (Touchie, 2013). Approximately 50% of total antibiotic prescriptions for preschool children are unnecessary, with 20% being attributed to URIs (Clavenna & Bonati, 2011;Maor et al, 2011).…”
Section: Introductionmentioning
confidence: 99%